HPLC‐QTOF method for quantifying 11‐ketoetiocholanolone, a cortisol metabolite, in ruminants' feces: Optimization and validation. Issue 18 (1st August 2018) - Molina‐García, Lucía; Pérez, Jesus M.; Sarasa, Mathieu; Ureña‐Gutiérrez, Benjamín; Espinosa, Jose; Azorit, Concepción
Abstract: Studies of animal ecology can benefit from a quantified understanding of eco‐physiological processes and, in particular, of the physiological responses in free‐ranging animals to potential stressors. The determination of fecal cortisol metabolites as a noninvasive method for monitoring stress has proved to be a powerful tool. High‐performance liquid chromatography coupled with tandem mass spectrometry (HPLC‐MS/MS) has emerged as the most accurate method for avoiding problems related to the nonspecificity of immunoassays. In this study, we optimize and validate a reliable method using HPLC‐MS/MS for quantifying 11‐ketoetiocholanolone (11‐k), a representative fecal cortisol metabolite in ruminants. An appropriate extraction and purification procedure was developed taking into account the complex nature of feces. The final extract obtained was then analyzed with HPLC‐MS/MS using a quadrupole‐time‐of‐fly (QTOF) tandem mass spectrometer with an electrospray ionization interface operating in positive mode, which allowed an unequivocal determination of the metabolite due to its accurate mass capabilities. After rigorous optimization of both sample extraction and the HPLC‐QTOF parameters, making use of feces from free‐ranging Iberian ibex, ideal conditions were established. Matrix‐matched standards were used to calibrate the method. The limit of detection and quantification was 13‐ and 40‐ ng/g, respectively. The validation of the method was performed with recoveries in the range of 85–110%, a figure much higher than the 60% obtained with the previous extraction methods used in our laboratory, and with relative standard deviations (RSDs) no higher than 15% for the complete analytical procedure, including extraction and analysis. The time required for the fecal 11‐k analysis was greatly reduced in comparison with the previous work carried out in our laboratory. This is the first time that QTOF mass detection coupled with HPLC has been validated for 11‐k quantification in feces from free‐ranging ruminants such as Iberian ibex. Given the high selectivity and sensitivity attained, our method could become a useful tool for noninvasive stress quantification in ruminants. Abstract : Studies on animal ecology can benefit from a quantified understanding of ecophysiological processes and, in particular, of the physiological responses in free‐ranging animals to potential stressors. The determination of faecal cortisol metabolites as a means of monitoring stress has proven to be a powerful tool. We develop, optimize and validate a reliable method using HPLC‐MS/MS for quantifying 11‐ketoetiocholanolone (11‐k), a representative faecal cortisol metabolite, in ruminants. This method avoids problems related to the non‐specificity of immunoassays. Given that 11‐k is a cortisol metabolite commonly found in faeces and the high specificity and sensitivity attained, the method developed could become useful for non‐invasive stress quantification in other species.